DIAGNOSTIC CRITERIA OF RHINOSINUSITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
Rhinosinusitis is a common and often misdiagnosed inflammatory condition affecting the nasal cavity and paranasal sinuses. Accurate diagnosis is crucial for effective treatment and to prevent complications. This article reviews the current diagnostic criteria for rhinosinusitis, differentiating between acute and chronic forms, and highlights the clinical, radiological, and laboratory methods used in modern otorhinolaryngological practice.